A note on noncosingular lifting modules - Amouzegar, Kalati T.; Keskin, Tütüncü D. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Let $R$ be a right perfect ring. Let $M$ be a noncosingular lifting module which does not have any relatively projective component. Then $M$ has finite hollow dimension.